2000
DOI: 10.1161/01.atv.20.12.e134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mast Cell–Dependent Conversion of Cultured Macrophages Into Foam Cells With Antiallergic Drugs

Abstract: Abstract-Degranulation of isolated, rat peritoneal mast cells in the presence of low density lipoprotein (LDL) induces cholesteryl ester accumulation in cocultured macrophages with ensuing foam cell formation. This event occurs when the macrophages phagocytose LDL particles that have been bound to the heparin proteoglycans of exocytosed granules. In an attempt to inhibit such foam cell formation pharmacologically, rat peritoneal mast cells that had been passively sensitized with anti-ovalbumin-IgE were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…When mast cells were activated by intraperitoneal administration of C48/80, a laboratory-use mast cell activator, LDL uptake by macrophages rose by 7~24-fold [94]. Like 48/80-triggered mast cell stimulation, lgE-dependent stimulation of sensitized mast cells also leads to increased uptake of LDL by cocultured macrophages, and thereby foam cell formation [95, 96]. In contrast, the mast cell stabilizer cromolyn effectively blocked mast cell–dependent LDL uptake by macrophages [95].…”
Section: Mast Cells In Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…When mast cells were activated by intraperitoneal administration of C48/80, a laboratory-use mast cell activator, LDL uptake by macrophages rose by 7~24-fold [94]. Like 48/80-triggered mast cell stimulation, lgE-dependent stimulation of sensitized mast cells also leads to increased uptake of LDL by cocultured macrophages, and thereby foam cell formation [95, 96]. In contrast, the mast cell stabilizer cromolyn effectively blocked mast cell–dependent LDL uptake by macrophages [95].…”
Section: Mast Cells In Dyslipidemiamentioning
confidence: 99%
“…Like 48/80-triggered mast cell stimulation, lgE-dependent stimulation of sensitized mast cells also leads to increased uptake of LDL by cocultured macrophages, and thereby foam cell formation [95, 96]. In contrast, the mast cell stabilizer cromolyn effectively blocked mast cell–dependent LDL uptake by macrophages [95]. Along with LDL particles, high-density lipoprotein (HDL) particles constantly pass from the bloodstream into the arterial intima [91].…”
Section: Mast Cells In Dyslipidemiamentioning
confidence: 99%
“…Among the evidence collected so far it has been demonstrated that mast cells stabilized in vitro, using anti-allergic drugs, were able to, inhibit foam cell formation suggesting a direct role in plaque development (Ma and Kovanen, 2000). In accordance, several lines of in vivo research have demonstrated that aortic lipid accumulation in atherosclerosis-prone mice is reduced, when the mice have been genetically engineered to be mast cell-deficient, or when mast cell activation in mast cell-sufficient mice has been pharmacologically inhibited.…”
Section: Mast Cell Mediated Atherosclerosis Progressionmentioning
confidence: 99%
“…Pharmacological stabilization of mast cells with their inhibitor, cromolyn (disodium cromoglycate, DSCG), reduced mast cell activation-induced atherosclerotic plaque intraplaque hemorrhage, macrophage apoptosis, vascular leakage, and CXCR2/VLA-4 (Very Late Antigen-4)-mediated recruitment of leukocytes in apolipoprotein E-deficient ( Apoe −/− ) mice [55]. Mast cell stabilizers MY-1250 and cromolyn also can prevent mast cell-mediated macrophage foam cell formation in vitro [56]. We showed that mast cell stabilization with cromolyn reduced elastase perfusion-induced AAA [54], which suggests that mast cell-derived cytokines, growth factors, proteoglycans, chymases and tryptases, or other proteases — such as cysteinyl cathepsins and MMPs — participate directly and indirectly in the pathogenesis of atherosclerosis and AAA.…”
Section: Chymases and Tryptases In Cardiovascular Diseasesmentioning
confidence: 99%